Analisis Strategi Pengembangan Usaha @Mac.schol Kabupaten Semarang - Wibi Lambang (Jurnal Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
In implementing the right competitive advantage strategy to be implemented by a business, entrepreneurs need to look at market conditions and assess their position in the market. This can be done by analyzing the business environment, both internal and external, which is commonly called a SWOT analysis. The purpose of this research is to formulate a better business development strategy. This study uses a qualitative descriptive method with data collection techniques through interviews and observation and documentation. Primary data collection was carried out through in-depth interviews with informants in this study, namely the owner of @mac.schol, employees and consumers in the Semarang area and its surroundings. While the secondary was collected through literature and previous research journals. The research method used in this study is the SWOT analysis method. From the results of IFAS and EFAS, the business position is in quadrant 1, from this quadrant, the recommended strategy is an aggressive/progressive strategy. Then from the SWOT matrix the right alternative that can be applied at @mac.schol going forward is the SO strategy by maintaining business strengths and minimizing weaknesses and avoiding threats seen from internal and external factors through a SWOT analysis matrix. Keywords: SWPT analysis, strengths, weaknesses, opportunities, threats.